Catalytic three-component C–C bond forming dearomatization of bromoarenes with malonates and diazo compounds. Issue 33 (7th August 2020) - Kato, Hiroki; Musha, Itsuki; Komatsuda, Masaaki; Muto, Kei; Yamaguchi, Junichiro
Abstract : A catalytic three-component C–C bond forming dearomatization of bromoarenes was developed, enabling rapid access to multi-substituted alicycles. Abstract : A Pd-catalyzed dearomative three-component C–C bond formation of bromoarenes with diazo compounds and malonates was developed. Various bromoarenes ranging from benzenoids to azines and heteroles were transformed to the corresponding substituted alicyclic molecules. The key to this reaction is the generation of a benzyl–palladium intermediate, which reacts with malonates to form a Pd– O -enolate species. Strikingly, the present method enabled rapid access to multi-substituted alicycles through subsequent elaboration of dearomatized products.